ANALISIS TITIK PULANG POKOK USAHA KUE PIA PADA INDUSTRI RUMAH TANGGARONI DI KOTA PALU - Katuwu, Sukanda; Effendy, Effendy; Lamusa, Arifuddin (AGROTEKBIS, 2018)
Agricultural sector in agribusiness insight with its role in national economy provides some excellences that could be considered. Given the nature of agricultural products which are perishable so agroindustry role is indispensable. Mung bean is one of the most popular food in Indonesia, with the scientific name Phaseolus radiates L, which can be found in almost in every region in Indonesia. According to the large number of this agricultural commodity, the opportunity to open a business of refined products is wide open. “RONI” Industrial Pia Cake is one of the household scale businesses which produceMung Bean Pia in Palu City. This business has one product which is Mung Bean Pia, being sold around regions in Palu. This research aims to identify the amount of earned revenue, production output, and sales value received on condition of break even point. This research was conducted at Zebra 5 number 1 street, South Palu District, Palu City of “RONI” household scale business for two months which is from May to June 2016. The data used consist of primary data and secondary data. Primary data were obtained by observation and direct interviews with respondents, namely the business leaders and one of the employees, while secondary data were obtained from literature that are relevant to the purpose of the study. The results showed that revenues of Cake Pia